Analisis Perspektif Guru Fisika SMA Di Banda Aceh Dalam Pembelajaran Daring: Sulitkah Pembelajaran Daring? - Agung Novesa Hidayat; Nurulwati Nurulwati; Evendi Evendi; Arief Muliandi (U-Teach: Journal Education of Young Physics Teacher, 2021)
The impact of the COVID-19 pandemic has affected various fields of life, including education, resulting in changes to the learning system. The purpose of this research is to analyze the difficulties experienced by physics teachers during learning online. The sample in this study was 8 physics teachers with the criteria of 2 male teachers and 6 female teachers with the specifications of 6 senior teachers and 2 junior teachers. The research method used a quantitative approac h with an instrument in the form of a questionnaire to analyze the difficulties of physics teachers in online learning, the analytical model used is interactive analysis. The results of this study illustrate that in general physics teachers in Banda Aceh have difficulty in teaching online. The most dominant difficulties are the lack of motivation and interest of students, student participation, and the difficulty of conveying abstract physics concepts. It is hoped that further research can examine the strategies that can be offered to physics teachers in online learning.